Principal support for student psychological needs: A social-psychological pathway to a healthy learning environment. Issue 5 (7th August 2017) - Adams, Curt; Olsen, Jentre
Abstract : Purpose: Although leadership evidence highlights the importance of cooperative principal-teacher relationships, research has not looked thoroughly at the content behind principal-teacher interactions. The purpose of this paper is to use self-determination theory and organizational conversation to develop principal support for student psychological needs (PSSPN), a concept that represents principal-teacher interactions based on social and psychological factors contributing to student learning. The empirical part of the study tests the relationship between PSSPN and faculty trust in students and student self-regulated learning. Design/methodology/approach: Hypotheses were tested with a non-experimental, correlational research design using ex post facto data. Data were collected from 3, 339 students and 633 teachers in 71 schools located in a metropolitan area of a southwestern city in the USA. Hypotheses were tested with a 2-2-1 multi-level mediation model in HLM 7.0 with restricted maximum likelihood estimation. Findings: Principal support for student psychological needs had a positive and statistically significant relationship with faculty trust in students and self-regulated learning. Additionally faculty trust mediated the relationship between principal support for student psychological needs and self-regulated learning. Originality/value: This is one of the first studies to examine school leadership by the content that is exchanged during principal-teacher interactions. Principal support for student psychological needs establishes a theoretically-based framework to study leadership conversations and to guide administrative practices. Empirical results offer encouraging evidence that the simple act of framing interactions around the science of wellbeing can be an effective resource for school principals.